Novel anti-inflammatory film as a delivery system for the external medication with bioactive phytochemical “Apocynin” - Anter HM; Abu Hashim II; Awadin W; Meshali MM (Dove Medical Press, 2018)
Hend Mohamed Anter,1 Irhan Ibrahim Abu Hashim,1 Walaa Awadin,2 Mahasen Mohamed Meshali1 1Department of Pharmaceutics, Faculty of Pharmacy, Mansoura University, Mansoura, Dakahlia, Egypt; 2Department of Pathology, Faculty of Veterinary Medicine, Mansoura University, Mansoura, Dakahlia, Egypt Purpose: Recently, Apocynin (APO) has emerged as a bioactive phytochemical with potent antioxidant and anti-inflammatory properties. No reports have been published so far concerning its topical application as a pharmaceutical dosage form for prospective use. To the best of our knowledge, this is the first study to fabricate novel anti-inflammatory film for external medication with APO. Methods: APO film was prepared using casein (CAS) as a natural protein film former by solvent casting technique. The medicated film was extensively evaluated in terms of its various physicochemical characteristics, ex vivo skin permeation profile, stability, and finally in vivo anti-inflammatory activity on carrageenan-induced rat paw edema. Results: The film represented satisfactory mechanical properties along with good flexibility. Fourier transform-infrared spectroscopy, differential scanning calorimetry, and X-ray diffractometry revealed possible solubility of APO in the amorphous CAS and inter- and intramolecular hydrogen bonding between the film components. The ex vivo skin permeation results of the medicated film demonstrated non-Fickian diffusion mechanism of the permeated drug. Application of APO film to rat paw before carrageenan-induced paw edema or after induction disclosed eminent anti-inflammatory activity expressed by marked decrease in paw swelling (%) and increase in edema inhibition rate (%). In addition, histopathologic examination revealed a significant decrease in inflammatory scores. The immunohistochemical expression levels of both nuclear factor kappa B and cyclooxygenase-2 were significantly suppressed. Conclusion: These results indicated that CAS film could be applied as a promising external delivery system for the anti-inflammatory APO. Keywords: Apocynin, casein, topical film, in vivo studies, inflammation, pharmacodynamics